Red Hat Certified System Administrator (RHCSA) - Vugt, Sander van (LiveLessons (Indianapolis, Ind.), 2016)
Learn solid fundamental Linux operating system skills with Beginning Linux System Administration LiveLessons. Taught by best-selling author and trainer Sander van Vugt, Beginning Linux System Administration LiveLessons walks you through the essential system administration tasks you need to know to get up and running in Linux quickly. This 12 lesson video course starts with the basics, from determining which distribution is right for you to walking through the steps of installing Linux on the two most popular flavors: Ubuntu and Red Hat. Next, you will connect to Linux and really get your feet wet, using an editor and working with files. You will then dive into managing permissions, processes and software before working with logs, exploring Linux security and finally managing services. Red Hat Certified System Administrator (RHCSA) Complete Video Course is an engaging self-paced video training solution that provides learners with more than 16 hours of personal visual instruction from an RHCSA and RHCE certified expert with more than 20 years of practical Linux teaching experience. Through the use of topic-focused instructional videos you will gain an in-depth understanding of the Red Hat Certified Administrator (RHCSA) exam as well as a deeper understanding of Red Hat Enterprise Linux so you master the key foundational principles of systems administration. Included with the product are dynamic and interactive hands-on exercises and quizzes designed to test your knowledge while you study. The course includes 100% coverage of exam objectives, hands-on exercises included with each lesson so you can practice what you learned in a real CLI environment, multiple-choice quizzes to help you test your knowledge, and hands-on exercises to give you the extra edge you need to excel on the exam. Red Hat Certified System Administrator (RHCSA) Exam Prep Workshop contains more than 4 hours of deep-dive training on common RHCSA exam traps, pitfalls, and difficulties. Sander van Vugt, an experienced Red Hat instructor, trainer, and author will detail the most common mistakes people make when taking the exam, so you can avoid them in the testing facility. You will then walk through a live practice exam with the author in real time, so you can experience first-hand what it's like to take the test.